Fixed effects regression models - Allison, Paul D. (Sage University papers / Quantitative applications in the social sciences, 2009)
1. Introduction -- 2. Linear Fixed Effects Models: Basics -- The Two-Period Case -- Extending the Difference Score Method for the Two-Period Case -- A First-Difference Method for Three or More Periods per Individual -- Dummy Variable Method for Two or More Periods per Individual -- Interactions With Time in the Fixed Effects Method -- Comparison With Random Effects Models -- A Hybrid Method -- 3. Fixed Effects Logistic Models -- The Two-Period Case -- Three or More Periods -- Interactions With Time -- A Hybrid Method -- Methods for More Than Two Categories on the Response Variable -- 4. Fixed Effects Models for Count Data -- Poisson Models for Count Data With Two Periods per Individual -- Poisson Models for Data With More Than Two Periods per Individual -- Fixed Effects Negative Binomial Models for Count Data -- A Hybrid Approach -- 5. Fixed Effects Models for Events History Data -- Cox Regression -- Cox Regression With Fixed Effects -- Some Caveats -- The Hybrid Method for Cox Regression -- Fixed Effects Event History Methods for Nonrepeated Events -- 6. Structural Equation Models With Fixed Effects -- Random Effects as a Latent Variable Model -- Fixed Effects as a Latent Variable Model -- A Compromise Between Fixed Effects and Random Effects -- Reciprocal Effects With Lagged Predictors -- Appendix 1. Stata Programs for Examples in Chapters 2 to 5 -- Appendix 2. Mplus Programs for Examples in Chapter 6